Kepemimpinan Strategis Indonesia melalui "Diplomasi Vaksin" dalam Mengamankan Stok Vaksin Nasional dan Global - Patricia Prajogo; Hikmat Zakky Almubaroq; Wirandita Gagat Widyatmoko; Langgeng Gilang Pangestu (Journal of Education on Social Science (JESS), 2022)
In the spirit of recovering from the impact of the Covid-19 pandemic, the world faces various obstacles in adapting to new normal. The insufficient amount of knowledge on how to respond the pandemic had caused the handling of Covid-19 crises that impacts many sectors are carried out independently by each country. Vaccine nationalism by each country leads to vaccine's scarcity and creates unequal access to vaccines between developed and developing countries. The scarcity of a crucial public goods such as vaccines show that the world is indeed in lacks of solidarity and leadership to say the least. With strategic leadership theory, this study seeks to see Indonesia's efforts to encourage the emergence of solidarity between countries through various platforms of international relations. By qualitative methods, this research shows that Indonesia's leadership role is the key to bringing countries together to get out of the Covid-19 pandemic and encourage fair distribution of vaccines.